The influence of WeChat use on driving behavior in China: A study based on the theory of planned behavior. (September 2020) - Qu, Weina; Ge, Yan; Guo, Yuxiu; Sun, Xianghong; Zhang, Kan
Highlights: A prospective and systematic study of WeChat use while driving on the functional differentiation of WeChat among Chinese drivers, different from the previous study of calling and texting. Drivers' attitudes can effectively predict whether they will send texts, listen to voice messages, and send and browse pictures on WeChat while driving. Drivers' attitudes cannot effectively predict whether they will read texts or send voice messages on WeChat while driving. The drivers' intention of using WeChat while driving is the best direct predictor of actual behavior. Moral norms have significant negative influence on actual behavior, while group norms can positively predict actual behavior. Abstract: Driving has become common, and distracted driving, especially that caused by WeChat use, is a significant cause of traffic crashes. Based on the theory of planned behavior, this study analyzes self-reports from a sample of 286 drivers from China to explore the influence of different WeChat functions on driving behavior. The analyses reveal that the intention to use WeChat while driving can substantially predict the use of WeChat while driving. Moreover, drivers' attitudes can effectively predict whether they will send texts, listen to voice messages, and send and browse pictures on WeChat while driving. However, drivers' attitudes cannot effectively predict whether they will read texts or send voice messages on WeChat while driving. In recent years, WeChat has become a popular messaging software, and many drivers use it. Therefore, it is important and necessary to raise awareness among drivers about the dangers of using WeChat while driving.